2016
DOI: 10.1021/acsnano.6b02110
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide Nanoclusters: Aqueous, Concentrated, Stable, and Catalytically Active Colloids toward Green Chemistry

Abstract: Increasing attention has been dedicated to the development of nanomaterials rendering green and sustainable processes, which occur in benign aqueous reaction media. Herein, we demonstrate the synthesis of another family of green nanomaterials, layered double hydroxide (LDH) nanoclusters, which are concentrated (98.7 g/L in aqueous solvent), stably dispersed (transparent sol for >2 weeks), and catalytically active colloids of nano LDHs (isotropic shape with the size of 7.8 nm as determined by small-angle X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 60 publications
4
67
0
3
Order By: Relevance
“…This offers a tremendous range of possibilities to produce LDH materials on demand. By playing on the synthetic parameters, particle sizes can be tuned in a large extend ranging from nanoclusters, to several microns . Thanks to hard and soft templating approaches, phase separation phenomenon and miniemulsion, peculiar LDH morphologies displaying enhanced meso and macroporosity, have been recently described such as microspheres, fibrous structures, inverse opals and macroporous monoliths …”
Section: Specific Features Of Ldh Matricesmentioning
confidence: 99%
“…This offers a tremendous range of possibilities to produce LDH materials on demand. By playing on the synthetic parameters, particle sizes can be tuned in a large extend ranging from nanoclusters, to several microns . Thanks to hard and soft templating approaches, phase separation phenomenon and miniemulsion, peculiar LDH morphologies displaying enhanced meso and macroporosity, have been recently described such as microspheres, fibrous structures, inverse opals and macroporous monoliths …”
Section: Specific Features Of Ldh Matricesmentioning
confidence: 99%
“…There have also been reports on the preparation of very small metal hydroxide nanoparticles (particle size: 5–8 nm) using propylene oxide for pH control and organic additives at a low temperature (20–40 °C) . On the basis of this method, single‐component metal hydroxide nanoparticles composed of various metal cations and Ni‐Al LDH nanoparticles have been prepared. However, if this method is applied to the preparation of Mg‐Al LDH nanoparticles, Al(OH) 3 may be produced as an impurity as a result of the gradual increase in pH .…”
Section: Introductionmentioning
confidence: 99%
“…50) Recently, the author and coauthors reported the synthesis of a soft-templated mesoporous LDH film from LDH nanoclusters and an amphiphilic polymer (Pluronic surfactant). 38) Although the mesophase is less ordered compared to those of the previously-reported oxide systems, better structural ordering of mesophase is further expected by decreasing the size of LDH NBBs; the size of LDH particle used in the report is 7.8 nm, whereas the sizes of NBBs for the oxides are less than 46 nm. 48),51) The mechanism of the formation of LDH nanoclusters is versatile and the process can be extended to CoAl, ZnAl, and LiAl LDHs.…”
Section: Scheme Ii: Hydroxide Nanoclusters and Their Use As Nanobuildmentioning
confidence: 70%
“…38) The synthesis was performed via a facile one-pot route. Briefly, NiCl 2 ·6H 2 O, AlCl 3 ·6H 2 O, and acetylacetone (acac) were dissolved in a mixture of ethanol and ultra-pure water.…”
Section: Scheme Ii: Hydroxide Nanoclusters and Their Use As Nanobuildmentioning
confidence: 99%